Construction and Demolition Waste Management in a Developing Country: A Nigerian Scenario - Ogunseye, Nathaniel Oluwaseun; Ogunseye, Omololu David; Ogunseye, Abiodun Olanrewaju (Journal of Sustainability Perspectives, 2023)
Construction and demolition waste (CDW) is an important waste composition receiving attention from policymakers and researchers globally due to the negative impacts associated with its management. This paper explores construction and demolition waste management (CDWM) in Nigeria with a view to understanding CDWM’s practices as perceived by the policymakers, waste managers and other stakeholders in the construction industry. A descriptive qualitative research design was adopted with data obtained from secondary sources. Findings revealed that CDWM is not a recent phenomenon in Nigeria but there is a renewed interest in it in the last decade. Findings also revealed that CDW does not receive the deserved attention from the constituted authority and stakeholders in the construction industry. While there is a low level of awareness regarding the negative impacts of CDW on public health and the environment, most construction firms and contractors have resorted to unsustainable disposal methods of open dumping, burning, and landfilling. Further findings revealed the potential for sustainable CDWM of reusing, recycling, and composting. Finally, the paper put forward recommendations that would chart a course for sustainable CDWM in Nigeria if implemented.